2014
DOI: 10.1021/jp411299e
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Hydrogen and Carbon Monoxide on Pd–Au Bimetallic Surfaces

Abstract: Pd−Au bimetallic catalysts have shown potential applications in numerous heterogeneous reactions in which hydrogen and CO act as reactants, intermediates, or products. A fundamental understanding of the interplay between coadsorbed H and CO on the Pd−Au surface is necessary for improving the understanding of catalytic performance. In this study, the interactions of hydrogen and CO with Pd/Au(111) model surfaces were investigated by temperature-programmed desorption (TPD) and molecular beam scattering (MBS) exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 67 publications
(135 reference statements)
1
30
0
Order By: Relevance
“…52,[56][57][58] The growth of the Pd overlayer on the Au(111) surface at 77 K has been suggested to obey a layer-by-layer mechanism. 52,[56][57][58] The growth of the Pd overlayer on the Au(111) surface at 77 K has been suggested to obey a layer-by-layer mechanism.…”
Section: Model Catalyst Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…52,[56][57][58] The growth of the Pd overlayer on the Au(111) surface at 77 K has been suggested to obey a layer-by-layer mechanism. 52,[56][57][58] The growth of the Pd overlayer on the Au(111) surface at 77 K has been suggested to obey a layer-by-layer mechanism.…”
Section: Model Catalyst Experimentsmentioning
confidence: 99%
“…7,36,40 As the annealing temperature is increased, the surface Pd morphology is transformed from a mixture of isolated and contiguous sites to a surface containing only isolated Pd sites. 52,57 The deposition rate of Pd was calibrated with a quartz crystal microbalance (QCM) controller (Maxtek Inc.) assuming a thickness of 1 ML Pd equals 0.274 nm. 52,57 The deposition rate of Pd was calibrated with a quartz crystal microbalance (QCM) controller (Maxtek Inc.) assuming a thickness of 1 ML Pd equals 0.274 nm.…”
Section: Model Catalyst Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it is known that Pd(111) and Au(111), respectively, bind to H strongly and weakly, 20,21 while the PdAu(111) surfaces have a H binding energy intermediate to Pd and Au. 8,17,22 Our previous studies have shown that TPD can differentiate the H 2 desorption peaks from Pd(111)-like and Pd-Au interface sites on PdAu(111) single-crystals, 16,[22][23][24][25][26] but TPD cannot differentiate the sizes and geometries of Pd or Pd-Au ensembles due to an overlap of the desorption peaks. However, it was found from density functional theory (DFT) calculations that different sizes and geometries of Pd(111)-like and Pd-Au interface sites have different selectivities and activities for catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%